Pengaruh Pendidikan Kesehatan Tentang Pemeriksaan Payudara Sendiri Terhadap Pengetahuan Dan Motivasi Melakukannya Pada Wanita Usia 30-50 Tahun Di Desa Joho Mojolaban - Sari, Agissia Citra; , Arina Maliya, S.Kep ., Msi.Med; , Kartinah, A.Kep., S.Kep (2016)
Cancer is a major health problem in the world even in Indonesia. Most deaths are caused by cancer on women is breast cancer. Breast cancer can be prevented by breast self-examination (BSE) which is one way of efficient and effective as an early detection of breast cancer in addition to mammography. Breast self-examination can be done all the women independently without the cost to do it in order to get a sign of breast cancer at earlier stages of disease (down staging). The purpose of this study was to determine the effect of health education on breast self-examination (BSE) to knowledge level and motivation in women aged 30-50 years in Joho village, Mojolaban. This research was a quantitative research. The method was used quasi-experimental method with non-equivalent control group approach. The sampling technique was used Multistage sampling with 40 respondents were divided into two groups, the treatment group were given health education and the control group were not given health education. Data analysis using Wilcoxon Signed Rank test and Mann Whitney test with α= 0,05. The result of this study is treatment group showed the value of knowledge's pretest (14,55) and posttest (17,10), the value of motivation's pretest (59.45) and posttest (65,45). In the control group showed the value of knowledge's pretest (14,05) and posttest (14,25), the value of motivation's pretest (59,20) and posttest (59,65). The result of differences test in knowledge after health education showed an average value of treatment group greater than the control group (17,10>14,25) and motivation's average value of treatment group greater than the control group (65,45>59,65). Knowledge of different test results showed p-value=0,001 and motivation showed p-value=0,002. From the results of this study concluded that health education on breast self-examination affect knowledge level and motivation in women aged 30-50 years in Joho village, Mojolaban.